Moth flies (Diptera, Psychodidae) from Portugal with descriptions of a new genus, new species and additions to the fauna of the Iberian Peninsula - Wagner, Rüdiger; Andrade, Rui; Gonçalves, Ana (Zootaxa, 2022)
Collections of Psychodidae in Portugal revealed a number of new species and a new genus for this country and the Iberian Peninsula. New species described are: Pneumia portuguesa sp. nov., Ulomyia iberica sp. nov., Clytocerus ibericus sp. nov., Pericoma estrelica sp. nov., and Psychoda iucunda sp. nov.. Heteroberdeniella gen. nov. is proposed with Berdeniella jaramensis (Wagner) as type species and Heteroberdeniella guardarramica sp. nov. is also included. Most species and genera are members of the West Palearctic fauna, but the genus Mystropsychoda Duckhouse is mentioned for the first time out of the Afrotropical realm. Distribution patterns of several genera and species cover at least the Mediterranean area and in addition indicate biogeographic relationships to the Afrotropical realm and particularly the East African mountain chains.